Trailblazing multi-material structure: Niobium alloy to tungsten–copper composite using wire-arc additive manufacturing - Abdul Karim, Md; Jeon, Yongho; Bong Kim, Duck (Materials Letters, 2024)
Integrating tungsten and niobium alloys into a single component offers synergistic benefits for fusion reactor applications. Additive manufacturing, particularly for components with complex geometries, further amplifies these advantages. This study examines the fabricability of a multi-material structure composed of a W–Cu composite and an Nb–Zr alloy using wire-arc additive manufacturing. The resulting W–Cu/Nb–Zr structure was free from significant defects like porosity or cracks, though the formation of hard intermetallic compounds was observed. Numerical analysis indicated considerable residual stress accumulation at the interface. During tensile testing, fractures occurred in the W–Cu composite near the interface, with the specimens exhibiting an ultimate tensile strength of 218 ± 3 MPa and an elongation of 5.7 ± 1 %.
Keywords: Complex geometries; Fabricability; Multi-material structure; Single components; Strength; Tungsten-copper composites; W-Cu composites; Wire arc; Wire-arc additive manufacturing; Zr alloys; Niobium; Refractory alloy; Residual stress; Strength; Tungsten; Wire-arc additive manufacturing